Flexural behaviour of concrete slabs reinforced with GFRP bars and hollow composite reinforcing systems. (15th March 2020) - Al-Rubaye, Mohammed; Manalo, Allan; Alajarmeh, Omar; Ferdous, Wahid; Lokuge, Weena; Benmokrane, Brahim; Edoo, Azam
Abstract: Glass Fibre Reinforced Polymer (GFRP) bars are now attracting attention as an alternative reinforcement in concrete slabs because of their high resistance to corrosion that is a major problem for steel bars. Recentlyhollow concrete slab systems are being used to reduce the amount of concrete in the slab and to minimise the self-weight, but the internal holes makes them prone to shear failure and collapse. A hollow composite reinforcing system (CRS) with four flanges to improve the bond with concrete has recently been developed to stabilise the holes in concrete members. This study investigated the flexural behaviour of concrete slabs reinforced with GFRP bars and CRS. Four full-scale concrete slabs (solid slab reinforced with GFRP bars; hollow slab reinforced with GFRP bars; slab reinforced with GFRP bars and CRS; and slab reinforced with steel bars and CRS) were prepared and tested under four-point static bending to understand how this new construction system would perform. CRS is found to enhance the structural performance of hollow concrete slabs because it is more compatible with GFRP bars than steel bars due to their similar modulus of elasticity. A simplified Fibre Model Analysis (FMA) reliably predicted the capacity of hollow concrete slabs.